Improved Retention Characteristics of Pd-Nanocrystal-Based Nonvolatile Memories by a Simple Timing Technique. (30th September 2015) - Kang, Tsung-Kuei; Chen, Yun-Feng; Lin, Cheng-Li; Wang, Fang-Hsing; Liu, Han-Wen; Chien, Feng-Tso; Shi, Jen-Bin
Abstract : By controlling the different initial time of Hf and Al precursor supply, the proposed Hfx Aly Oz tunneling layer with different Al/Hf ratios from 0.21 (top) to 0.06 (bottom) can be fabricated. Regarding Al/SiO2 /Pd nanocrystals/proposed Hfx Aly Oz /Si, the proposed Hfx Aly Oz film can prevent stress from Pd nanocrystals and achieve a higher electron current during programming. Regarding the retention characteristics, the final memory windows of 2.5/2.05 V at 25/90°C can be obtained, respectively. Programmed and erased with ±10 V/100 ms, the device shows a memory window of 2.4 V after 10 4 cycles for a 25°C test.